Aircraft maintenance tecnicians certificating procedure in Turkey - Özen, Mustafa (Univerzita Pardubice, 2010)
The air transportation rules are strictly edited worldwide, as in Europe and in Turkey. Turkey has participated several international organizations; such as International Civil Aviation Organization (ICAO), European Civil Aviation Conference (ECAC), Joint Aviation Authorities (JAA), and so on. All of these memberships force Turkey to prepare national aviation legislation as convenient as international rules. These international rules can be updated so they must be followed and if it is necessary national rules also must be updated. The aim of this paper is to discuss the importance of qualified aircraft maintenance technicians. For that reason; first, international aviation technicians qualification rule (EASA Part 66/JAR 66) is examined then, national legislation is examined. It is found that aircraft maintenance technicians’ certification procedure is same as EASA Part 66/JAR 66 requirements. It is also found that EASA Part 66/JAR 66 rule is transferred to Turkey’s national legislation as a need of JAA membership. It is obtained that there are no significant differences between international and national legislations. However, both legislations do not cover the old license conversion problem which has a great importance. It is concluded that qualified aircraft maintenance technicians are the key factor for sustainable air transportation.
Keywords: air transportation; aircraft maintenance; aircraft maintenance technician